2008
DOI: 10.1159/000156958
|View full text |Cite
|
Sign up to set email alerts
|

Centrilobular Fibrosis: An Underrecognized Pattern in Systemic Sclerosis

Abstract: Background: The impressive association of lung involvement and gastroesophageal reflux in scleroderma raises the possibility of a cause-effect relationship. Objectives: To determine clinical, radiological and histopathological features of systemic sclerosis (SSc) patients according the presence or absence of centrilobular fibrosis (CLF). Methods: Twenty-eight SSc patients with lung involvement were submitted to open lung biopsy and the specimens classified for the presence of CLF (bronchocentric distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 61 publications
3
41
0
4
Order By: Relevance
“…In patients with CLF alone and treated exclusively with intensive antireflux therapy, the lung disease remained stable for a period of 1 year. (26) In the present study, the prevalence of GERD was 35.7%, and 77.7% of the patients presented at least one typical GERD symptom. Although this prevalence rate is high in relation to that observed in the general population, most studies using esophageal pH-metry in IPF have demonstrated even higher prevalence rates.…”
Section: Resultssupporting
confidence: 47%
“…In patients with CLF alone and treated exclusively with intensive antireflux therapy, the lung disease remained stable for a period of 1 year. (26) In the present study, the prevalence of GERD was 35.7%, and 77.7% of the patients presented at least one typical GERD symptom. Although this prevalence rate is high in relation to that observed in the general population, most studies using esophageal pH-metry in IPF have demonstrated even higher prevalence rates.…”
Section: Resultssupporting
confidence: 47%
“…Some studies have suggested that GOR may contribute to idiopathic pulmonary fibrosis [8,9] and SSc-ILD [10-12] through repeated microaspiration of gastric content into the respiratory tract. Other arguments supporting this hypothesis are the preferential localisation of SSc-ILD in the lower lung zones [19] and the frequent centrilobular localisation of fibrosis in SSc patients with GOR [21]. However, the preliminary studies provide a low level of evidence due to their cross-sectional design or short follow-up periods, small numbers of patients and, in some studies, absence of multivariate analysis.…”
Section: Lung Involvement Of Systemic Disease M Gilson Et Almentioning
confidence: 99%
“…The histopathological characteristics of microaspiration-related changes have been poorly studied. Bronchiolocentric organizing pneumonia, foreign bodies, intraluminal basophilic content have been described in surgical lung biopsies of ILD-SSc with possible microaspiration (16,17). However, those histological features probably represent a small subgroup of ILD-SSc, while the vast majority of these patients show "pure" non specific interstitial pneumonia (NSIP) histopathologic pattern and GER is virtually present in all.…”
Section: The Role Of Pepsinmentioning
confidence: 99%